Uma aplicação da congruência na determinação de critérios de divisibilidade - Silva, Luis Henrique Pereira da (2015)
This work aims to demonstrate in a practical way the divisibility criteria 2-97 in sieve Eratostenes with cutting the right and the left, based on the method of multiplication and division Egyptian. The entire process is demonstrated using the divisibility to whole numbers, greatest common divisor, prime numbers, decomposition in prime factors and matching.